Helicobacterpylori eradication following endoscopic resection might prevent metachronous gastric cancer: a systematic review and meta-analysis of studies from Japan and Korea - Yu, Tian-Hang; Bai, Dan; Liu, Kai; Zhang, Wei-Han; Chen, Xin-Zu; Hu, Jian-Kun (Frontiers in Medicine, 2024)
The systematic review and meta-analysis was performed to evaluate the preventive effectiveness of Helicobacter pylori eradication against metachronous gastric cancer (MGC) or dysplasia following endoscopic resection (ER) for early gastric cancer (EGC) or dysplasia. Methods: PubMed, Cochrane Library, MEDLINE and EMBASE were searched until October 31, 2023, and literatures of randomized controlled trials or cohort studies were peer-reviewed. The incidence of metachronous gastric lesions (MGLs) including MGC or dysplasia were compared between Helicobacter pylori persistent and negative groups, between eradicated and negative groups, and between eradicated and persistent groups.Results: Totally, 21 eligible studies including 82256 observations were analyzed. Compared to those never infected, Helicobacter pylori persistent group (RR=1.58, 95% CI 0.98-2.53) trended to have higher risk of MGLs and significantly in partial subgroups, while post-ER eradicated group (RR=0.79, 95% CI 0.43-1.45) didn't increase risk of MGLs. Moreover, successful post-ER eradication could significantly decrease the risk of MGLs (RR=0.54, 95% CI 0.44-0.65) comparing to those persistently infected. Sensitivity analysis obtained generally consistent results, and no significant publication bias was found.The persistent Helicobacter pylori infection trends to increase the post-ER incidence of MGC or dysplasia, but post-ER eradication can decrease the risk correspondingly. Post-ER screening and eradication of Helicobacter pylori has preventive effectiveness on MGC, and should be all-included recommended to post-ER patients.